2015
DOI: 10.14798/73.2.812
|View full text |Cite
|
Sign up to set email alerts
|

THREATENED FISHES OF THE WORLD: Botia dario (Hamilton, 1822) (Cypriniformes: Cobitidae)

Abstract: Bengal loach Botia dario is a valuable food fish in South Asian countries including Bangladesh, Bhutan, India and Nepal. However, the wild population is declining due to heavy harvest, habitat loss and its ecological changes. This paper suggests actions for the conservation of the lasting isolated populations of B. dario in Asian countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Previously it was abundant in rivers, lakes, canals and reservoirs (Pethiyagoda et al., ), but now the wild populations are declining due to various ecological changes to their habitat (Hossain, Hossain, Islam, et al., ; Hossain, Hossen, Ahmed, et al., ; IUCN Bangladesh, ; Mijkherjee, Praharaj, & Das, ). Therefore, it is categorized as vulnerable in Bangladesh (IUCN Bangladesh, ); lower risk near threatened in India (Balasundaram, Arumugam, & Murugan, ); threatened in Sri‐Lanka (IUCN Sri‐Lanka, ); and globally recognized as list concern (IUCN, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously it was abundant in rivers, lakes, canals and reservoirs (Pethiyagoda et al., ), but now the wild populations are declining due to various ecological changes to their habitat (Hossain, Hossain, Islam, et al., ; Hossain, Hossen, Ahmed, et al., ; IUCN Bangladesh, ; Mijkherjee, Praharaj, & Das, ). Therefore, it is categorized as vulnerable in Bangladesh (IUCN Bangladesh, ); lower risk near threatened in India (Balasundaram, Arumugam, & Murugan, ); threatened in Sri‐Lanka (IUCN Sri‐Lanka, ); and globally recognized as list concern (IUCN, ).…”
Section: Introductionmentioning
confidence: 99%
“…D. pusilla and L. bata are important target species in Bangladesh for small‐ and large‐scale fishers, who use a variety of traditional fishing gear. The populations of these two important species are in decline as a result of overexploitation, habitat loss and other ecological changes (Hossain et al., , ; Hossain, ; Hossen et al., ) and are listed in Bangladesh as endangered (IUCN Bangladesh, ).…”
Section: Introductionmentioning
confidence: 99%
“…The populations of N. soroides in the wild has been decreasing due to the spawning difficulties (Junior et al, 2005), and overfishing (Rumondang and Mahari, 2017) such has been reported in the previous study in another fresh water fish (Hossain et al, 2015). Another factors like water pollution (Kottelat et al, 1996), habitat degradation, and associated, and illegal loging are also threatening the fish populations (Afrose and Ahmed, 2016;Gupta et al, 2015;Hossain et al, 2015).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 86%